Approaches for FACTS optimization problem in power systems - Jordehi, Ahmad Rezaee (IEEE, 2012)
This paper discusses thoroughly about different methods for solution of flexible AC transmission systems (FACTS) optimization problem in power systems. First, it explains the requirements of an ideal solution for FACTS optimization problem, then classifies the methods used by researchers in four main groups as classical methods, technical methods, heuristics and mixed methods, and discusses thoroughly about characteristics, advantage s and disadvantages of each group of methods. Finally, some tips are offered for future research on this area.